Looking at Citizens Indonesia's Local Wisdom through Law Sociological Approach for Efforts to Maintain the Richness of Nation - Debora Aswinda Solin; Wisnu Pratama Iryanto (The Indonesian Journal of International Clinical Legal Education, 2019)
This paper employs a law sociological approach to explore and analyze the local wisdom of Indonesian citizens, aiming to understand its role in preserving the cultural richness of the nation. By delving into the intricate interplay between local customs and legal frameworks, the study sheds light on how traditional practices contribute to the social fabric. The research emphasizes the significance of recognizing and integrating local wisdom into legal considerations for fostering a harmonious coexistence of cultural diversity within Indonesia. Through this interdisciplinary lens, the paper advocates for an inclusive legal framework that not only respects but actively incorporates the indigenous knowledge and practices of the citizens, thereby contributing to the sustainable preservation of the nation's cultural heritage.